Answer :

Let’s take x as : 1,2,3,4

And respectively y as : -1,-2,-3,-4


For x = 1 and y = -1:


(x + y) = (1 - 1) = 0


(x - y) = (1 – (-1)) = 2


For x = 2 and y = -2:


(x + y) = (2 - 2) = 0


(x - y) = (2 – (-2)) = 4


For x = 3 and y = -3:


(x + y) = (3 - 3) = 0


(x - y) = (3 – (-3)) = 6


For x = 4 and y = -4


(x + y) = (4 - 4) = 0


(x - y) = (4 – (-4)) = 8


(i) (x + y) – x = y


Let’s check for x = 1 and y = -1


L.H.S = (1 + (-1)) – 1


= (0) – 1


= -1


R.H.S = y


= -1


= L.H.S


Hence, it holds for x = 1 and y = -1


Let’s check for x = 2 and y = -2


L.H.S = (2 + (-2)) – 2


= (0) – 2


= -2


R.H.S = -2


= L.H.S


Hence, it works for x = 2 and y = -2


Similarly we can check for other values too. It will follow.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Taking diffKerala Board Mathematics Part II

Taking diffKerala Board Mathematics Part II

Taking diffKerala Board Mathematics Part II